Energy Efficiency and Aesthetics in Bamboo Architecture Based on Balinese Local Wisdom - Sastrawan, I Wayan Wirya; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin; Yudantini, Ni Made (Universitas Ibn Khaldun Bogor, 2025)
Bamboo has been recognized as a sustainable building material with high tensile strength, rapid growth, and a low carbon footprint. In Bali, traditional architecture reflects cultural values and local wisdom that prioritizes spatial harmony, natural ventilation, and symbolic ornaments. This research explores how passive design strategies can optimize energy efficiency in bamboo-based architecture while maintaining traditional Balinese elements' aesthetic integrity. By integrating the principles of Tri Hita Karana and Asta Kosala Kosali, this study uses Building Information Modeling (BIM) simulation methods, community perception surveys, and energy efficiency analysis to evaluate the sustainability and resilience of a bamboo-based architectural culture. The study results show that applying Balinese spatial configuration in bamboo construction improves natural ventilation, reduces energy consumption, and maintains cultural identity. The study provides a framework for integrating traditional Balinese architectural principles with sustainable modern design, thus maintaining cultural continuity in the face of contemporary architectural demands.